Promotive effect of cancer-testis antigen CT57 on proliferation, invasion, migration and epithelial-mesenchymal transition of liver cancer cells - LUO Lange; ZHENG Chao; LEI Ming (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the effect of cancer-testis antigen family member CT57 on proliferation, migration and invasion of the human liver cancer cells and tumorigenesis in nude mice, and the possible mechanism. Methods·Bioinformatics methods were used to analyze the differential expression of CT57 in several cancer tissues and normal tissues, and its effect on the prognosis of liver cancer patients. Lentiviral vectors were used to establish liver cancer cell lines with stable knockdown and overexpression of CT57, which were confirmed by Western blotting. CCK-8 cell proliferation assay, soft agar colony formation assay and cell cycle experiment were used to detect the effect of CT57 on the proliferation and colony formation ability of liver cancer cells. Wound healing and Transwell assays were used to detect the effect of CT57 on the migration and invasion of liver cancer cells, and the expression of epithelial-mesenchymal transition (EMT) markers was detected by quantitative real-time PCR (qRT-PCR). To explore the effect of CT57 on liver cancer cells in vivo, CT57 knockdown liver cancer cells (experimental group) and control liver cancer cells (control group) were used to conduct subcutaneous tumor formation experiments in nude mice. Results·Bioinformatics analysis of multiple tumors and corresponding normal tissues in The Cancer Genome Atlas Program (TCGA) database showed that CT57 was highly expressed in most tumor tissues, including liver cancer, and the expression level of CT57 was significantly correlated with the prognosis of liver cancer patients. Cell proliferation assay, soft agar colony formation assay, and cell cycle experiment showed that knockdown of CT57 inhibited the proliferation and colony formation of liver cancer cells and led to cell cycle arrest. In wound healing and Transwell assays, knockdown of CT57 inhibited the invasion and migration of liver cancer cells, while overexpression of CT57 promoted it. The results of qRT-PCR indicated that overexpression of CT57 resulted in downregulation of epithelial cell markers ECAD (E-cadherin) and OCLN (occludin), and upregulation of mesenchymal cell markers VIM (vimentin), TWIST1 (twist family bHLH transcription factor 1), and MMP2 (matrix metallopeptidase 2). In the in vivo experiments, knockdown of CT57 significantly reduced the tumor formation rate of liver cancer cells, tumor volume, and tumor weight in nude mice. Conclusion·Knockdown of CT57 leads to cell cycle arrest, thereby inhibiting the proliferation of liver cancer cell and subcutaneous tumorigenesis in nude mice; CT57 promotes the invasion, migration and EMT of liver cancer cells.